The Development and Validation of Self-evaluated Employability Inventory for TVET Hearing-impaired Graduates - Seh Sheh, Yong; Tze Kiong, Tee; Hanapi, Zaliza (International Journal of Psychosocial Rehabilitation, 2019)
Work is important for the sustainability and well-being of life. Just like ordinary hearing people, a hearing-impaired person also has desires to be appreciated in successful careers with value lifestyle. This achievement can be measured by employability. The purpose of this paper is to discuss on the development of a selfevaluated employability inventory for hearing-impaired community. Using a modified Delphi method, nine panel experts were appointed to obtain consensus to construct items for this inventory. Three rounds of modified Delphi method was conducted, which the first round was a one-to-one interview session. Twenty items’ inventory was developed based on the information that gathered from interviews and literature searches. The Second and third round were using questionnaire survey in a way to get experts’ rating for each item. The collected data were analysed empirically using content validity ratio (CVR). The Finding showed 10 items retained to assess hearingimpaired self-evaluated employability. This inventory also can be interchangeably evaluated by employer to his/her employee.